Analytic Approaches and Critical Practices: On What We Can Learn. Issue 3 (1st December 2020) - Di Summa, Laura T.
Abstract: This article investigates the relationship between philosophical accounts of criticism, largely within the analytic tradition, and the practice of criticism. Specifically, I am interested in the performative, subjective, and often idiosyncratic nature of such a practice and in the advantages it can deliver in the understanding of works of mass art, in the inquiry over the nature of aesthetic judgments, and in initiating aesthetic appreciation. Promoting such a connection is also, in turn, a way of at least partially bridging the divide between analytic approaches and the kind of work more typically conducted by scholars in film studies.